The Development and Application of Microwave Heating - Cao, Wenbin (IntechOpen, 2012)
Microwave heating has found many applications ranging from the microwave ovens in kitchen to heat food, to a sterilization apparatus for medical treatment, to materials processing in the various fields. In those applications, microwave heating demonstrates significant advantages over conventional methods in reduced processing time and less environmental impacts. This book is comprised of eight chapters within three parts highlighting different aspects covering both the basic understandings and the advanced applications. The included discussion on the application of microwave heating in the field of food-, chemical engineering-, agricultural-, forestry- and mineral processing industry will provide a passage for future research. As a monograph, it is designed to be a fundamental reference book, aiming to help the readers to concentrate on the key aspects behind the success in microwave heating.